2017
DOI: 10.3892/ol.2017.6398
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of CD24 expression, cell proliferation and migration, cisplatin-resistance, and caspase-3 expression during mesenchymal-epithelial transition induced by the removal of TGF-β1 in A549 lung cancer cells

Abstract: Abstract. Epithelial-mesenchymal transition (EMT) is a notable mechanism underlying cancer cell metastasis. Transforming growth factor β1 (TGF-β1) has been used to induce EMT; however, there is a lack of information regarding the role of TGF-β1 in mesenchymal-epithelial transition (MET). In the present study, EMT was induced in A549 lung cancer cells using TGF-β1 (TGF-β1-treated group) and MET was induced sequentially from the TGF-β1-treated group by removing the TGF-β1 (MET/return group). Untreated A549 lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Treating cells with different melatonin concentrations dependently reduced sphere formation (Figure A). Accumulating studies suggested that CD133 appeared to be a potential lung cancer stem cell marker . We also found that melatonin inhibits CD133 expression, according to data from the western blot and qPCR assay (Figure B).…”
Section: Resultssupporting
confidence: 68%
“…Treating cells with different melatonin concentrations dependently reduced sphere formation (Figure A). Accumulating studies suggested that CD133 appeared to be a potential lung cancer stem cell marker . We also found that melatonin inhibits CD133 expression, according to data from the western blot and qPCR assay (Figure B).…”
Section: Resultssupporting
confidence: 68%
“…While EMT most likely drives the escape of cancer cells from the primary tumor site, the reverse process, termed mesenchymal–epithelial transition (MET), is thought to drive the colonization at the distant metastatic site 40 , 41 . To explore whether the mesenchymal–epithelial plasticity affects the expression of ofCS on cancer cells, we removed TGF-β from the culture media of EMT-induced A549 cells 42 . Seventy-two hours after the removal of TGF-β, mesenchymal markers, such as fibronectin and N-cadherin, were reduced, indicating that the A549 cells had returned to a more epithelial state (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Combining chemotherapy drugs that act on different cell pathways could increase their individual effects against cell migration. Cisplatin can reduce A549 cell migration by acting through multiple pathways including those incorporating transforming growth factor β1 (TGF-β), Sox2, Wnt/β catenin signaling and the microRNA, miR-146a, through regulation of cyclin J [52,53,54]. However, the effect of cisplatin treatment against A549 migration can be mitigated by the development of resistance [52,55].…”
Section: Discussionmentioning
confidence: 99%